Analysis of Leadership Behavior Differences from Principles of Elementary School in Serangoon (Singapore) and Salatiga (Indonesia) - Fransiska Faberta Kencana Sari; Sri Marmoah (Universitas Kristen Satya Wacana, 2022)
The purpose of this study is to analyze the differences in leadership behavior of elementary school principals in Singapore and Indonesia based on behavioral approaches. The research was conducted with a case study qualitative design. Data collection techniques were carried out by using questionnaires and literature studies. The data were then analyzed by using inductive analysis techniques. The results of this study found differences in leadership behavior between principals in Singapore and Indonesia, where principals in Singapore led to the Team Management type of leadership behavior (9.9), while school principals in Indonesia led to the Authority-Compliance Management type of leadership behavior (9, 9). 1). This study then provides a study of the impact of each type of leadership behavior on school success. It is hoped that this study can be useful for school principals to be able to apply the type of leadership behavior of Team Management (9.9) which leads to optimization of educational attainment.